CONCEPT, RATIONALE AND GOALS OF SHAREHOLDER‘S DERIVATE ACTION - Mikalonienė, Lina (Teisė, 2015)
The shareholder’s derivative action has been transplanted into the Lithuanian Corporate Law (e.g. the Law on Stock Companies, Art. 16 str. part 1 par. 5), but has not received great interest from the national scholars. Analyzes of the shareholder’s derivative action starts with the key general aspects of the action, e.g. its concept, rationale and goals. It is concluded in the article that shareholder’s derivative action is used to protect different private interests. First, since the company’s claim is enforced, company’s interest as primary interest is protected. Second, shareholder’ locus standi is her subjective right, due to the reflective loss shareholder indirectly (derivatively) protects her own interests. To present a derivative action, violation of shareholder’s personal tangible interests is mandatory. Third, collective interests of all shareholders which may be affected equally by the action should be also taken into consideration. The rationale of the shareholder’s derivative action is to protect interests of minority shareholders as well as to control management of the company and ensure its better management. Compensation is the key goal of the derivative action.